Fiction et idéologie : Marx lecteur des Mystères de Paris - Alice de Charentenay; Anaïs Goudmand (Contextes)
This paper aims to explore Karl Marx's reading of The Mysteries of Paris, in chapters V and VIII of The Holy Family (1845). It is about analyzing the mechanisms of ideological commentary in this text : Marx's purpose is here to demonstrate that socialism claimed by Eugène Sue is in fact no more than a form of paternalism which reproduces bourgeois morality. However, beyond the intention announced by Marx, this chapters show the involvement of the future author of Capital in the story telling and his attachment to the characters. The link between the cognitive interest and the affective dimension of Marx's reading will be the specific subject matter of this study.